2020
DOI: 10.1007/s10389-020-01392-y
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and correlates of physical activity/inactivity and sedentary behaviour among high-school adolescents in Iran: a cross-sectional study

Abstract: Background Physical inactivity and sedentary behaviour are the main risk factors for non-communicable diseases in all stages of life. However, there is a lack of reliable data regarding the recommended level of physical activity and its correlates related to physical inactivity and sedentary behaviour among school students in Iran. The aim of the present study was to report the prevalence and correlates of physical activity/inactivity and sedentary behaviour among Iranian high school adolescents. Methods The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…[ 3 ] In a study in Iran, the prevalence of physical activity recommended by the World Health Organization among high school students is approximately 27.8%, about 72.2% of whom were not physically active, and the girl’s physical activity was lower than boys’. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] In a study in Iran, the prevalence of physical activity recommended by the World Health Organization among high school students is approximately 27.8%, about 72.2% of whom were not physically active, and the girl’s physical activity was lower than boys’. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…The previous study found that the socio-demographics of adolescents, such as gender, parental education, parental occupation, and parental income, are related to the adolescents' physical activity, generally. [14][15][16] Based on this description, the researchers want to determine the relationship between social determinants and physical activity among adolescents with the risk of obesity in rural areas of Indonesia.…”
Section: Introductionmentioning
confidence: 99%